Reciprocal regulation of interleukin‑17A and interleukin‑22 secretion through aryl hydrocarbon receptor activation in CD4 + T cells of patients with vitiligo - Liu, Baoyi; Xie, Yongyi; Mei, Xingyu; Sun, Yue; Shi, Weimin; Wu, Zhouwei (Experimental and therapeutic medicine, 2021)
Previous studies have shown the participation of the cytokines interleukin (IL) 17A and IL22 in the development of vitiligo. The aryl hydrocarbon receptor (AhR) functions in the pathogenesis of vitiligo and can modulate cytokine production. The aim of the present study was to determine the relationship between AhR activation and the secretion of IL17A and IL22 in CD4 T cells in vitiligo. A total of 20 newly diagnosed patients with progressive, unstable vitiligo and 20 healthy controls were recruited. CD4 T cells and skin samples were collected. Immunohistochemistry, ELISA, reverse transcription-quantitative PCR, western blotting and RNA interference experiments were performed. The expression of AhR was significantly lower in the CD4 T cells and skin, both lesional and nonlesional, of patients with vitiligo compared with healthy subjects. AhR expression was markedly lower in nonlesional compared with lesional skin of patients with vitiligo. The expression levels of IL17A and IL22 were significantly higher in patients with vitiligo compared with healthy subjects. Knockdown of AhR significantly increased the production of IL17A and markedly decreased IL22 levels in the CD4 T cells of patients with vitiligo. extract EGb 761 activated AhR, inhibited IL17A secretion and enhanced IL22 release in the CD4 T cells of patients with vitiligo. In conclusion, reduced AhR expression is associated with progressive, unstable vitiligo. Activation of AhR with extract EGb 761 may have therapeutic potential for decreasing IL17A levels and increasing IL22 levels in patients with vitiligo.